Analysis and damping of grid-forming converters interactions in bipolar HVDC connections using a coordinate transformation approach - Francesco Giacomo Puricelli; Pierre Rault; Carmen Cardozo; Jef Beerten (International Journal of Electrical Power & Energy Systems)
Substantial growth in bipolar Voltage Source Converter (VSC) -based High Voltage Direct Current (HVDC) connections is anticipated in the coming decade. Simultaneously, there is an expected increase in the adoption of Grid-Forming (GFM) strategies to control HVDC converters. However, concerns have arisen about potential interactions between GFM converters of a bipolar HVDC link placed at the same converter station due to their electrical proximity. This paper presents a coordinate transformation that separates the sub-synchronous interactions between the GFM converters as in-phase and anti-phase components. The insights offered by this transformation are presented through eigenvalue, and mode shape analyses, along with time-domain studies. Additionally, a novel centralized bipole synchronization control is introduced by combining the synchronization loops of the two GFM converters. Simulations demonstrate that the proposed control effectively mitigates undesirable sub-synchronous oscillations between the two GFM converters in the bipole while shaping their combined response to the AC system across different operational scenarios.